2021
DOI: 10.2147/ijgm.s342009
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metastasis in Patients with Small Cell Lung Cancer

Abstract: Purpose To characterize the risk factors for brain metastasis (BM) at presentation and analyze the prognostic factors for patients with small cell lung cancer (SCLC). Patients and Methods Patients were recruited from the SEER database between 2010 and 2016. They were divided into two groups according to BM status. The incidence trends of SCLC and its BM were analyzed by joinpoint software. The risk factors for BM in SCLC were identified by binary logistic regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…These were some unique disease features for elderly SCLC patients. In addition, we identified ten independent prognostic factors for OS and CSS, which were consistent with the previous findings [ 7 , 13 16 , 23 25 ]. Our model indicated that chemotherapy made the greatest contribution to the prognostic score.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These were some unique disease features for elderly SCLC patients. In addition, we identified ten independent prognostic factors for OS and CSS, which were consistent with the previous findings [ 7 , 13 16 , 23 25 ]. Our model indicated that chemotherapy made the greatest contribution to the prognostic score.…”
Section: Discussionsupporting
confidence: 91%
“…Our model indicated that chemotherapy made the greatest contribution to the prognostic score. Multiple studies have proved that chemotherapy, as the most important treatment for SCLC, can prolong the survival time of patients [ 7 , 13 , 15 , 23 , 26 ]. Our analysis also indicated that AJCC stage and surgery had greater impacts on patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results may be partially a consequence of the fact that more than 90% of patients received 6 cycles of chemotherapy, and 72.1% received subsequent treatment. Additionally, a lower proportion of patients in our study demonstrated brain metastases [12]. A separate study has showed the antitumor activity of anlotinib monotherapy in patients with refractory SCLC.…”
Section: Discussionmentioning
confidence: 44%